Introduction. - Guldin, Rainer (Flusser Studies, 2016)
The article introduces a section of articles that focus on the works of four authors including "Russia and Soul" by American artist Dale Pesmen; "Leaving Russia: A Jewish Story" by American scholar Maxim Shrayer; and "Little Failure" by American writer Gary Shteyngart.